Characterizing the Layer Structures of the Lacquerware From the Palace Museum by Terahertz Imaging in Reflection Geometry - Zhang, Hongfei; Zhao, Yuanmeng; Li, Chenyu; Zhang, Cunlin (Frontiers in Physics, 2021)
Chinese lacquerware is an important invention of arts and crafts in China. In this study, Chinese lacquerware is characterized using terahertz reflectometric imaging. The lacquerware studied herein comprises an ornamental wood panel covered by multiple layers of lacquers to portray motifs. For characterizing lacquerware, a terahertz time-domain spectroscopic reflectometric imaging system is proposed. The role of the proposed terahertz imaging system in highlighting the interface between layers during stratigraphic buildup in reflection geometry is proved. The proposed system provides a universal method for assessing the structural information of lacquered objects in a contactless and non-invasive manner; moreover, it provides two-dimensional images, subsurface three-dimensional images, and stratigraphic images (b-scans) in a contactless and non-invasive manner. Using the proposed system, we examine the buried layers of the lacquerware, including faults in the wooden layer and damages in the lacquerware. Research shows the promising prospects of terahertz time-domain spectroscopic reflectometric imaging as a non-destructive detection technique suited to lacquerware.